Potential Polygamous Breeding Behavior in Northern Bobwhite - Paul D. Curtis; Brad S. Mueller; Phillip D. Doerr; Charles F. Robinette; Theodore DeVos (National Quail Symposium Proceedings, 2017)
Breeding behavior ofradio-tagged northern bobwhite (Colinus uirginianus) was observed at Fort Bragg Military Reservation (n = 19), North Carolina, in 1985-88, and Tall Timbers Research Station (n = 27), Florida, during 1984-86. We observed apparent polygamous breeding behavior in 95% (18 of 19) of the radio-tagged northern bobwhite at Fort Bragg, and 93% (25 of 27) of the birds at Tall Timbers. We documented 5 cases of double-clutching by radio-tagged females. Twenty-seven percent of Fort Bragg clutches (n = 30), and 20% of Tall Timbers clutches (n = 56) were incubated by radio-tagged males. Northern bobwhite exhibited characteristics of both rapid multiclutch and am bisexual polygamous mating systems. Northern bobwhite are capable of uniparental care, have long breeding seasons, live in an environment with fluctuating resources, suffer high predation pressure during the nesting season, and raise precocial young; all traits that are similar to other bird species which have evolved polygamous mating systems.
Keywords: breeding behavior; Colinus virginianus; Florida; North Carolina; northern bobwhite; polygamy